A review of smart structures and adaptation of 3d printing methods for future fashion applications - Viktorija Diak (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The rapid advancement of innovative technological processes necessitates the fashion industry to contemplate novel perspectives it can offer. Additionally, the industry is progressively reducing its reliance on natural monofilaments and transitioning towards synthetic fabrics with new characteristics, employing intricate composites. The emergence of smart materials incorporating microencapsulation, shape-memory materials, and sensors responsive to external stimuli further contributes to this trend. Efforts are being made to incorporate wearable electronics in the form of flexible multifunctional devices. However, the creation of such novel materials/structures and their integration with traditional fibres present numerous challenges, urging the industry to explore new manufacturing methods. This review primarily focuses on actively developing types of passive intelligent structures discovering their properties and advantages in relation to future clothing. Given that progress is achieved through programming and modifying the structures themselves using new materials/composites, prototyping plays a pivotal role as a problem-solving process. It involves searching for new production methods that can rapidly and cost-effectively help achieve desired outcomes. Presently, additive technologies represent one of the most successful and rapidly advancing alternative manufacturing methods. Consequently, they have been widely applied and actively developed in fields such as soft robotics, biomedical devices/sensors/fabrics, flexible wearable electronics, 4D printed structures, and other clothing components and accessories. The applicability of these technologies is illustrated in creating each specific type of smart structure under consideration by briefly describing 3D printing methods and providing examples of their usage. This serves to demonstrate how effectively and qualitatively they enable the prototyping of various multilayered structures and composites. Furthermore, these technologies hold the potential for integrating dissimilar processes, thereby facilitating the development of new smart fabrics with a significantly greater range of variations in the future. Overall, this article aims not only to demonstrate the suitability of additive technologies for smart structures but also to identify technological trends for future research in the fashion industry.